2022
DOI: 10.1186/s13065-022-00829-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new 2-(5-(5-nitrofuran-2-yl)-1,3,4-thiadiazol-2-ylimino)thiazolidin-4-one derivatives as anti-MRSA and anti-H. pylori agents

Abstract: In this work, we have synthesized twenty five new 2-(5-(5-nitrofuran-2-yl)-1,3,4-thiadiazol-2-ylimino)thiazolidin-4-one derivatives bearing an aryl or heteroaryl methylene group on position 5 of thiazolidinone and evaluated their antimicrobial activity against Gram-positive and -negative bacteria as well as three metronidazole resistant Helicobacter pylori strains. Most of the compounds were very potent towards tested Gram-positive bacteria and showed an antibacterial efficacy substantially greater than ampici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Compound 77 on the reaction with chloroacetyl chloride in dry toluene at 80-90°C gave intermediate 78, which was subsequently treated with ammonium thiocyanate in refluxing ethanol to afford 2-(5-(5-nitrofuran-2-yl)-1,3,4-thiadiazol-2-ylimino)thiazolidin-4-one 79. Finally, compound 79 was reacted with respective aromatic or heteroaromatic aldehydes in the acidic conditions to obtain the final compounds 80-104 (Figure 18) [14]. The findings of the MIC testing revealed that most compounds had more potent antimicrobial effects against MRSA, S. epidermidis and B. cereus than the reference antibiotic, ampicillin and compounds 90 and 101 were the most active.…”
Section: Literature Reports On Recent Developments In Furan Derivativ...mentioning
confidence: 99%
“…Compound 77 on the reaction with chloroacetyl chloride in dry toluene at 80-90°C gave intermediate 78, which was subsequently treated with ammonium thiocyanate in refluxing ethanol to afford 2-(5-(5-nitrofuran-2-yl)-1,3,4-thiadiazol-2-ylimino)thiazolidin-4-one 79. Finally, compound 79 was reacted with respective aromatic or heteroaromatic aldehydes in the acidic conditions to obtain the final compounds 80-104 (Figure 18) [14]. The findings of the MIC testing revealed that most compounds had more potent antimicrobial effects against MRSA, S. epidermidis and B. cereus than the reference antibiotic, ampicillin and compounds 90 and 101 were the most active.…”
Section: Literature Reports On Recent Developments In Furan Derivativ...mentioning
confidence: 99%